Penampilan Beberapa Galur Mutan Kacang Hijau Asal Irradiasi Sinar Gamma Cobalt-60 (M3) - Sri Hartati (Caraka Tani: Journal of Sustainable Agriculture, 2004)
Performance of Several Mungbean Lines Resulted from Mutation of Co-60 Gamma Rays Irradiation. Sri Hartati, 23 pages. The objectives of the research were to evaluate the agronomic traits of the fourth generation (M3) of mungbean mutants and to get at least one potential genotype for further selection in order to achieve a new high yielding variety. He research was done in Grumosol of Joho Mojolaban, Sukoharjo.The experimental design was completely randomized design with 12 treatments: G1/V1R0: the third generation of ‘Merpati’ with no radiation; G2/V1R1: the third generation of ‘merpati’ radiated at rate of 5 K rad; G3/ViR2: the third generation of ‘Merpati’ radiated at rate of 10 K rad; G4/V1R3: the third generation of ‘Merpati’ radiated at rate of 15 K rad; G5/V2R0: the third generation of ‘Camar’ with no radiation; G6/V2R1: the third generation of ‘Camar’ radiated at rate of 10 K rad; G7/V2R3: the third generation of ‘Camar’ radiated a rate of 15 K rad; G9/V3R0: the third generation of ‘Walet’ no with radiation; G10/V3R1: the third generation of ‘Walet’ radiated at rate of 5 K rad; G11/V3R2: the third generation of ‘Walet’ radiated at rate of 10 K rad; G12/V3R3: the third generation of ‘Walet’ radiated at rate of 15 K rad.The research conclude that weight of 1000 seeds and weight of seed per plot from the first to the fourth generation were achieved by ‘Walet’ variety irradiated at the rate of 10 K rad; and thus, this was the potential lines for further selection program.